2018
DOI: 10.1017/s1368980017003925
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status and maternal BMI are associated with duration of breast-feeding of Norwegian infants

Abstract: Our results show that duration of breast-feeding varies with socio-economic status and maternal BMI in Norway. Targeting groups with low socio-economic status and mothers with overweight or obesity is important, as they are less likely to breast-feed according to recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 21 publications
2
27
1
Order By: Relevance
“…The overall OR of being obese was significant (OR 1.47, 95% CI: 1.16-1.86) among 18 studies [71][72][73]75,80,85,[91][92][93]96,97,101,103,[109][110][111]113,117] but heterogeneity was substantial (I 2 = 93%, p for Q < 0.001,Tau 2 = 0.20). The subgroup analyses showed that the pooled risk among seven studies with a higher quality score [71,73,96,97,[101][102][103][104][105][106][107][108][109][110][111] (OR 1.71, 95% CI: 1.34-2.18; I 2 = 85%, p for Q < 0.001, Tau 2 = 0.06), and the risk among 16 studies with white ethnicity [71,73,75,80,85,[91][92][93]96,97,101,103,[109][110]…”
Section: Study Characterisicsmentioning
confidence: 95%
See 4 more Smart Citations
“…The overall OR of being obese was significant (OR 1.47, 95% CI: 1.16-1.86) among 18 studies [71][72][73]75,80,85,[91][92][93]96,97,101,103,[109][110][111]113,117] but heterogeneity was substantial (I 2 = 93%, p for Q < 0.001,Tau 2 = 0.20). The subgroup analyses showed that the pooled risk among seven studies with a higher quality score [71,73,96,97,[101][102][103][104][105][106][107][108][109][110][111] (OR 1.71, 95% CI: 1.34-2.18; I 2 = 85%, p for Q < 0.001, Tau 2 = 0.06), and the risk among 16 studies with white ethnicity [71,73,75,80,85,[91][92][93]96,97,101,103,[109][110]…”
Section: Study Characterisicsmentioning
confidence: 95%
“…I 2 = 29%, p for Q = 0.440, Tau 2 < 0.01; data not shown), and white ethnicity (n = [70,81,82,84,102,110,111]; HR 1.19, 95% CI: 1.09-1.29; I 2 = 14%, p for Q = 0.910, Tau 2 < 0.01; data n shown), confirming that overweight mothers had an increased risk of not continuing BF practic compared to normal weight mothers. On the other hand, the overall OR of being overweight on cessation was insignificant among 16 studies [69,[71][72][73][91][92][93]96,97,101,103,[109][110][111]116,117] w substantial heterogeneity (I 2 89%, p for Q <0.001, Tau 2 = 0.07). For studies that investigated obe mothers, overall HR was significant (HR 1.43, 95% CI: 1.22-1.69) among 10 stud [67,68,70,76,82,84,94,102,108,115] with substantial heterogeneity (I 2 68%, p for Q = 0.081, Tau 2 = 0.0 Such significance was also observed in the subgroup analyses including the six month assessment = 4 [67,82,94,102]; HR 1.66, 95% CI: 1.19-2.31; I 2 = 67%, p for Q = 0.102, Tau 2 = 0.08) and white ethnic (n = 7 [68,70,82,84,…”
Section: Study Characterisicsmentioning
confidence: 98%
See 3 more Smart Citations